Analyzing Students' Internal Problems in Learning English - Sulhairi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2025)
This study focuses on analyzing students' internal problems in learning English, as these significantly influence their academic success or failure in acquiring English as a foreign language. This study uses a qualitative methodology to get a deeper understanding of the internal problems faced by learners in English language learning at the beginning of their educational journeys. This research used a case study in Pariwisata program in the Second Grade (SMA). The students reported psychological challenges and diminished motivation, including low self-confidence, shyness, lack of interest in speaking, fear of public speaking, and apprehension over peer criticism, which led them to neglect studying and speaking English previously. The students' propensity for anxiety was significantly increased by psychological or cognitive illnesses. The study suggests that English is essential for enhancing the quality of learners' speaking proficiency.